Morin mitigate diethyl phthalate and bisphenol s - Induced hematotoxicity in rats model by abrogating oxidative stress - Ofem Effiom Eteng; Ceaser Antiya Moses; Chukwuka Uzoamaka Ogbonna; Abdulwasiu Oladokun Adeleye; Emmanuel Ifeanyichukwu Ugwor; Adewale Segun James; Esther Olamide Oladimeji; Adio Jamiu Akamo; Iwara Arikpo Iwara; Friday Effiong Uboh; Mbeh Eteng (Elsevier, 2022)
Endocrine disruptors affect biological systems, some as neglected home producing toxicity (NHPT). We investigated the effect of morin on diethyl phthalate (DEP) and bisphenol S (BPS)-induced hematotoxicity and oxidative stress using a rat model. Rats were exposed to DEP (50 μg/kg) and BPS (200 μg/kg) and treated with morin (25 and 50 mg/kg) by oral gavage for twenty-one days. Afterwards, they were sacrificed. Morin treatment significantly (p < 0.05) protected red blood cells and plasma membrane architecture by abolishing the DEP+BPS-induced decrease in the activity of all the hematological indices. Co-treatment with morin remarkably (p < 0.05) reversed DEP+BPS-induced decreases in glutathione levels, CAT, GPx, and SOD activities in red blood cells, while attenuating DEP+BPS mediated increase in hemato-oxidative damage markers (MDA and NO levels). Collectively, the different acute doses of morin might avert DEP and BPS-mediated hematotoxicity dysfunctions via its antioxidant, free-radical scavenging effect.